THE EFFECT OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL JUSTICE, AND ORGANIZATIONAL COMMITMENTS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT SMK YAYASAN PGRI JAKARTA TIMUR TEACHERS - Amelia, Dlya; Marsofiyati; Febriantina, Susan (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This research aims to determine the effect of organizational culture, organizational justice, and organizational commitment on organizational citizenship behavior (OCB). This research was conducted for seven months from February 2021 to September 2021. The population is 100 respondents, and the samples in this study is 80 respondents from Teachers at East Jakarta PGRI Foundation Vocational School. The sampling was done using proportional random sampling technic. The data was collected from a questionnaire via google forms using a Likert scale. To test the hypothesis proposed in this study, the technical analysis of the fit of the model used is Structural Equation Modeling (SEM) which is operated using the SmartPLS 3.0 program. The results showed that organizational culture, organizational justice, and organizational commitment had an effect on organizational citizenship behavior.